2015
DOI: 10.1088/1612-2011/12/11/115403
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear reflection of a nanosecond laser pulse from thin aluminum film in the temperature range 2–14 kK

Abstract: This letter aims to experimentally demonstrate the possibility of measuring the temporal dependencies of the surface temperature of an aluminum film confined by a transparent dielectric in the range below and above the critical temperature of aluminum (from 2 kK to 14 kK). Such temperatures are achieved under the action of a powerful linearly-polarized laser pulse of one nanosecond in duration onto the film's surface. To find the temporal dependencies of the temperature of the aluminum film the nonlinear refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…At first, a portion of the energy of a short laser pulse is reflected (nonlinear [19]) and another portion is absorbed (~20% [6]) in the gold layer and heats it and the thin neighboring layers of the glass and gel to high temperatures. An estimate in [6] showed that at E = 20 µJ the temperature of such a system can reach 10 4 K at the end of the laser pulse.…”
Section: Laser Printing In Lems Technologymentioning
confidence: 99%
“…At first, a portion of the energy of a short laser pulse is reflected (nonlinear [19]) and another portion is absorbed (~20% [6]) in the gold layer and heats it and the thin neighboring layers of the glass and gel to high temperatures. An estimate in [6] showed that at E = 20 µJ the temperature of such a system can reach 10 4 K at the end of the laser pulse.…”
Section: Laser Printing In Lems Technologymentioning
confidence: 99%
“…The film thicknesses for two samples differ from each other no more than 20 nm. The dependencies ( ) T t , ( ) p t and ( ) ρ t are obtained taking into account the nonlinear reflection of the incident laser pulse [22]. The significant decrease of the reflection coefficient R of aluminum takes place within the time interval min is observed at the instant t for which the condition τ ≈ t / 1 0 is fulfilled.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature ( ) T t of the aluminum film within the central area of the laser spot is determined using the measured instant power of the thermal radiation and the reflection coefficient at the instant t. The last one is determined as the ratio of the instant power of the reflected and the incident laser pulse. It should be noted that the dependence of the light reflection coefficient of aluminum on the incident laser power is nonlinear [22]. The validity of the calibration of the pyrometer is verified using the values of the melting temperature of refractory metals.…”
Section: Materials and Experimental Setupmentioning
confidence: 89%